Financing healthcare services: a qualitative assessment of private health insurance schemes in Ghana - Angela Asante; Richard A. Bonney; Peter Twum (BMC Health Services Research)
Abstract Background Health financing in Ghana aims for universal access to healthcare, with both public and private insurance schemes playing vital roles. The National Health Insurance Scheme (NHIS) addresses out-of-pocket expenses but faces enrollment and trust issues. However, 12 licensed Private Health Insurance Schemes (PHISs) offer complementary services, enhancing healthcare access and quality through additional coverage and service delivery. This study aimed to assess the operations and performance of PHIS in Ghana. Methods The research utilized a qualitative descriptive design, focusing on registered PHIS providing services to Ghanaians. A convenient sampling technique was employed for data collection. Data was gathered through face-to-face interviews with participants until saturation was achieved. The data was thematically analyzed. Results The study highlights the intricate regulatory framework governing PHISs in Ghana, emphasizing licensing and accreditation requirements. It revealed diverse operational strategies, including nationwide coverage and tailored policies for different clientele. Benefit packages varied, with distinct plans like the “X-scan plan” for medical imaging. Payment structures ranged from upfront payments to flexible options. PHIS’s growth was driven by health concerns during the COVID-19 pandemic, strategic investments, and partnerships. Clientele for PHIS primarily resides in urban areas, focusing on sectors like education. Conclusion The study assesses Ghana’s PHI sector, highlighting its critical role in financing healthcare in Ghana. Findings reveal PHIS’s diverse packages and flexible payments boost healthcare access and quality. We, therefore, recommend PHIS foster partnerships with National Health Insurance Authority (NHIA) accredited facilities, reduce non-payment risks, and ensure transparency to foster trust and accurate risk assessment, promoting sustainable growth and reliability in Ghana’s Private Health Insurance (PHI) industry.